História da arte em Portugal - Carlos Alberto Ferreira de Almeida, Mário Jorge Barroca, Vítor Serrão (Presença)
1.º vol: "O Românico", Carlos Alberto de Almeida, 190 p.; 2.º vol: "O Gótico", Mário Jorge Barroca, 303 p.; 4.º vol: "O Barroco", Vítor Serrão, 303 p.